A family case of hereditary olivopontocerebellar atrophy: features of diagnosis and course of the disease - Mishura, Svitlana; Turchyna, Natalia; Heletiuk, Yuliia (The Ukrainian Scientific Medical Youth Journal, 2024)
OPCA is a heterogeneous group of degenerative ataxias, the common feature of which is the occurrence of changes in the lower olives of the medulla oblongata, nuclei and transverse fibers of the pons, and cerebellar cortex. OPCA is not explicitly considered in general epidemiological surveys on spinocerebellar syndromes. It was described that in Cantabria (Spain) the prevalence ratios of autosomal-dominant cerebellar ataxia (ADCA) and idiopathic late-onset cerebellar ataxia (ILOCA) were 1.2 and 2.2 cases per 100,000, respectively. Some 60% of patients included in these groups had a «cerebellar-plus» syndrome and their computed tomographic (CT) or magnetic resonance imaging (MRI) scans revealed cerebellar and brainstem atrophy, allowing a presumptive diagnosis of OPCA. According to these estimations, the prevalence ratio of OPCA is about 2 per 100,000 (Berciano, 1991). The clinical picture is characterized by significant inter- and intra-familial polymorphism. Symptoms of the disease start to appear, usually at the age of 30-40, in the form of a disorder of coordination and unsteadiness when walking quickly (later, with the progression of the disease, a typical ataxic gait starts to develop). At the same time, intentional tremor and dyscoordination of hands appear, and in some cases – an asynergy of facial muscles. Speech disorders manifest themselves quite early and have a severe cerebellar-dysarthric character. An important place in the diagnosis of OPCA belongs to neuroimaging methods — CT, and MRI (the presence of an atrophic process and the absence of focal changes in the brain parenchyma). One of the factors that confirms the diagnosis is the presence of a family history and the relentlessly progressive nature of the disease.